The BCI Glossary: a first proposal for a community review. Issue 3 (3rd July 2021) - Antonietti, Alberto; Balachandran, Pradeep; Hossaini, Ali; Hu, Yaoping; Valeriani, Davide
ABSTRACT: The description of Brain-Computer Interfaces (BCI) can lead to confusion because of the high heterogeneity of devices, protocols, and applications. Besides, different professional categories are involved: end-users, clinicians, therapists, and engineers; each one having different conceptions of BCI-related terms. This can cause misunderstandings and errors, and it makes it impossible to compare different systems and their performances. The IEEE P2731 working group has been working on a standardized glossary for BCI research, together with a functional model for BCI. Here, we are presenting a first version of the BCI glossary, generated by the collective effort of the working group. One hundred fifty-three terms have been identified to be critical for describing in a standardized way BCI systems and their related aspects (e.g., the neurophysiological characteristics of the neural signals recorded). Each term has been provided with a definition, merged from multiple ones proposed by working group members, with appropriate references to the current state of the art. Finally, we are asking for feedback and suggestions about this first version of the BCI glossary to the wider community of BCI users and researchers. External inputs will improve the glossary, which will become, after further revisions, an official IEEE standard.